NEEDS ANALYSIS FOR ESP COURSE DEVELOPMENT FOR UNDERGRADUATE ENGINEERING STUDENTS - Rahayu, Intan Sinta Dewi (2016)
Abstract This research is aimed at finding out the target needs, in terms of necessities and lacks, relevant to engineering work context, and investigating the learning needs as the route to meet the target needs. A cross-sectional survey as research design was employed. The data were gained from the semi-structured interview to three representatives of English lecturers for engineering and the questionnaire to ninety fourth-year engineering students in the Faculty of Engineering in one of universities in Bandung. The results reveal that engineering students' English proficiency has not met the target needs provoked by the majority lacks of communication skill, particularly speaking fluently and giving an oral presentation. With this in mind, some preferred-learning needs to overcome the lacks are the significance use of a good combination material, the use of internet as a media, working in a small group and in pair as learning partner, having a simulation related to engineering work context, problem solving, and an oral presentation. This research is expected to contribute towards the Faculty of Engineering in developing and evaluating the English course design relevant to the current demand and English lecturers in planning and conducting instruction in line with engineering students' preference in learning English;--- Penelitian ini bertujuan untuk mengetahui kebutuhan sasaran, yang mencakup kebutuhan dan kelemahan, yang berhubungan dengan konteks pekerjaan keahlian teknik, dan mengetahui kebutuhan pembelajaran sebagai cara untuk mencapai kebutuhan sasaran. Penelitian ini menggunakan survey kros-seksional. Hasil penelitian menunjukkan bahwa kemampuan bahasa Inggris mahasiswa teknik belum memenuhi kebutuhan sasaran yang disebabkan oleh kelemahan terbesar dalam kemampuan berkomunikasi, terutama berbicara dengan lancar dan presentasi dalam bahasa Inggris. Oleh karena itu, untuk mengatasi kelemahan tersebut, beberapa kebutuhan belajar bahasa Inggris yang dipilih mahasiswa adalah pentingnya penggunaan materi yang dikombinasikan dengan baik, penggunaan internet sebagai media, belajar dalam kelompok kecil dan pasangan sebagai teman belajar, simulasi yang berhubungan dengan konteks pekerjaan teknik, penyelesaian masalah, dan presentasi dalam bahasa Inggris. Penelitian ini diharapkan dapat berkontribusi terhadap Fakultas Teknik dalam mengembangkan dan mengevaluasi rencana pembelajaran bahasa Inggris yang sesuai dengan tuntutan saat ini, dan untuk dosen bahasa Inggris dalam menrencanakan dan mengimplementsikan rencana pembelajaran sesuai dengan preferensi mahasiswa teknik dalam belajar bahasa Inggris.